1991
DOI: 10.1097/00000658-199101000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal Abscess in Regional Enteritis

Abstract: Intra-abdominal abscess (IAA) developed in 129 of 610 patients (21.2%) with Crohn's disease confined to the small bowel. The location of the abscess was intraperitoneal (IPA) in 109 (17.9%) and retroperitoneal (RPA) in 20 (3.3%). There was a marked preponderance of male patients in the retroperitoneal group (ratio, 18:2) (p less than 0.0001). All 129 patients were operated on. Thirteen of one hundred nine patients (12%) with IPA were reoperated on for recurrent abscess, and nine (8.2%) for other reasons. Exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…Reports from Europe and the United States on the same subject note that the incidence of abscess ranges from 10% to 30% in patients with CD; 1-5 the complication of an abscess occurred at a mean age of 35 years; 5 the duration of illness (CD) preceding the abscess formation was 4 to 16 years. [2][3][4][5] These studies concluded that the incidence of an abdominal abscess increased in proportion to the duration of CD. 12,13 However, no reports refer to the cumulative incidence of abscess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports from Europe and the United States on the same subject note that the incidence of abscess ranges from 10% to 30% in patients with CD; 1-5 the complication of an abscess occurred at a mean age of 35 years; 5 the duration of illness (CD) preceding the abscess formation was 4 to 16 years. [2][3][4][5] These studies concluded that the incidence of an abdominal abscess increased in proportion to the duration of CD. 12,13 However, no reports refer to the cumulative incidence of abscess.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature from western countries, its occurrence is between 10% and 30%, [1][2][3][4][5] but in Japan, the only study on the subject, presented by Maeda et al, 6 who conducted a survey by questionnaire, reported that the incidence was 8.9%. Many of the patients with abscess formation complicating CD were subjected to surgical treatment: only a few have been treated with conservative methods.…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime risk for intraabdominal abscess in CD patients is approximately 25%. 121 Almost all abscesses require drainage either surgically or percutaneously. Although there is controversy as to whether or not intraabdominal CD abscess should be managed surgically, surgical resection is required when an abscess has enteric contents.…”
Section: Surgical Managementmentioning
confidence: 99%
“…20,21 Surgery remains an important component of treatment of CD and an accurate preoperative assessment of CD lesions and associated complications is required to plan the surgical approach and intervention. [22][23][24] Such preoperative assessment is even more important when using a laparoscopic approach that may limit the surgeons manual search for subtle lesions of the intestine.…”
mentioning
confidence: 99%